Back-Support Exoskeleton Control Strategy for Pulling Activities: Design and Preliminary Evaluation - Maria Lazzaroni; Tommaso Poliero; Matteo Sposito; Stefano Toxiri; Darwin G. Caldwell; Christian Di Natali; Jesús Ortiz (Designs, 2021)
The execution of manual material handling activities in the workplace exposes workers to large lumbar loads that increase the risk of musculoskeletal disorders and low back pain. In particular, the redesign of the workplace is making the execution of pulling activities more common, as an alternative to lifting and carrying tasks. The biomechanical analysis of the task revealed a substantial activation of the spinal muscles. This suggests that the user may benefit from the assistance of a back-support exoskeleton that reduces the spinal muscle activity and their contribution to lumbar compression. This work addresses this challenge by exploiting the versatility of an active back-support exoskeleton. A control strategy was specifically designed for assisting pulling that modulates the assistive torques using the forearm muscle activity. These torques are expected to adapt to the user’s assistance needs and the pulled object mass, as forearm muscle activity is considered an indicator of grip strength. We devised laboratory experiments to assess the feasibility and effectiveness of the proposed strategy. We found that, for the majority of the subjects, back muscle activity reductions were associated with the exoskeleton use. Furthermore, subjective measurements reveal advantages in terms of perceived support, comfort, ease of use, and intuitiveness.